Dynamic Bandwidth Allocation for NG-PONs with channel bonding - Zaouga, Aziza (2022)
Channel bonding is a recently proposed technique to provide higher aggregated line rates in NG-PONs by allowing ONUs to operate simultaneously in multiple wavelengths. On the other hand, the Dynamic Bandwidth Allocation (DBA) algorithm allocates to each ONU the grant time interval on each upstream frame that the ONU can use to transmit its data in the upstream direction. Channel bonding imposes a new challenge in the DBA algorithm as the grant time interval allocated to a ONU must be the same in all its channel-bonded wavelengths. In this work, we propose a new DBA algorithm for NG-PONs supporting data services which is a combination of a proportional fairness strategy and a max-min fairness strategy and guarantees the constraints imposed by channel bonding. We illustrate the merits of the new algorithm with two cases based on simulation. The results show that channel bonding can provide better QoS performance to data services even in cases where it is not strictly required.